The Role of AI in Driving Sustainable HRM: A Phenomenological Study on the Use of People Analytics for Corporate Carbon Footprint Reduction - Parinsi, Welimas Kristina; Musa, Anugrah Dewi Lestari; Musa, Kartika Septiary Pratiwi (Malaqbi Publisher, 2025)
This phenomenological study examines the role of artificial intelligence (AI) in advancing sustainable human resource management (HRM) practices, with a focus on reducing corporate carbon footprints through people analytics in Jakarta, Indonesia. As a megacity facing severe environmental degradation, Jakarta presents a critical context for exploring how AI-driven tools intersect with socio-cultural, ethical, and infrastructural realities. Through semi-structured interviews and focus group discussions with HR professionals and employees across diverse industries, the study reveals that while AI enhances precision in measuring emissions and optimizing eco-conscious workflows, its adoption is fraught with challenges. Key findings highlight tensions between technological efficiency and socio-economic inequities, ethical concerns over surveillance and algorithmic bias, and a pervasive